2014
DOI: 10.1186/1743-422x-11-143
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of porcine circovirus type 2 from piglets with Porcine Circovirus Associated Diseases in Colombia

Abstract: BackgroundThe porcine circovirus-associated disease (PCVAD) has been known since 1991 in Canada, but the first outbreak of PCVAD in Colombia was reported in 2007. In order to understand the molecular epidemiology of the disease and to establish the origin of the virus in the country, the study presented here intended to evaluate the presence of PCV2-associated systemic infection in piglets from different geographical regions over a period of 9-years (2002 -2010). The analysis included samples collected before,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In South America, PMWS and PCVAD have been reported; phylogenetic studies have only been conducted in Brazil, Argentina, Uruguay and Colombia [ 10 , 13 , 14 ]. The objective of this study is to evaluate the genetic diversity of PCV2 using sequences in pig affected by PMWS obtained from intensive swine farms in Chile.…”
Section: Introductionmentioning
confidence: 99%
“…In South America, PMWS and PCVAD have been reported; phylogenetic studies have only been conducted in Brazil, Argentina, Uruguay and Colombia [ 10 , 13 , 14 ]. The objective of this study is to evaluate the genetic diversity of PCV2 using sequences in pig affected by PMWS obtained from intensive swine farms in Chile.…”
Section: Introductionmentioning
confidence: 99%
“…If pigs are left unvaccinated for PCV-2, producers could see up to a US$20 loss per pig (Thacker 2013). High seroprevalences (82.4%) of pigs for PCV-2 antibodies have been reported in Canada (Liu et al 2002), the USA (80%) (Nawagitgul et al 2002), Taiwan (83.5%) (Wang et al 2004), Northern Ireland (>55%) (Walker et al 2000), and Columbia (83.6%) (Monroy et al 2014). In the present study, the overall seroprevalence for PCV-2 antibodies in T&T pigs was found to be 66%.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, DNA extractions were first performed from all serum samples collected using QIAamp DNA kit (QIAGEN®). Then PCV2 rep coding region of PCV2 was amplified using PCV2-ABF 5´GCCAGAATTCAACCTTMACYTTYC 3´ and PCV2-ABR 5´GCGGTGGACATGMTGAGATT 3´ primers, as previously described ( Rincón Monroy et al , 2014). PCR reactions were carried out in 20µl containing 5μl of DNA mixed with 15μl of real-time PCR master mix (Light Cycler® 480 SYBR Green I Master-Roche mix + 1μM of each primer) at 95°C for 1 minute followed by 40 cycles of 95°C for 1 minute, 61°C for 25 seconds and 72°C for 5 seconds.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the distant PCV2 genotype (PCV2e) is found in China ( Wang et al , 2009) and the USA ( Davies et al , 2016). In Colombia, PCV2 infections have been described since 2002 and have been recently characterized ( Rincón Monroy et al , 2014). …”
Section: Introductionmentioning
confidence: 99%